The goal-over-source asymmetry in Thai and Korean - Kultida Khammee; Seongha Rhee (Language and Cognition)
Thai and Korean have large inventories of adpositional particles, including source and goal markers. As reported in many languages, Thai and Korean adpositions also prominently exhibit the ‘goal-over-source asymmetry’ at multiple levels. This article supports this hypothesis on asymmetry from these two typologically and genealogically distinct languages. In both languages, goal markers far exceed source markers in number, confirming the hypothesis. Even among the allative-ablative-(locative) syncretic forms, the proportion of use for goal marking far exceeds that for source marking, again upholding the asymmetry hypothesis. The multiplicity of forms in the two polar categories is largely due to the stacking of multiple markers of (nearly-)synonymous adpositions as a strategy to reinforce meaning or to add finer shades of meaning. The multiplicity of forms is also due to frequent innovation of new forms, especially goal markers, in an effort to enhance expressivity and to entertain the desire for creativity. This is evident in the fact that the forms being innovated tend to carry more lexical content than older, fully grammaticalized forms, and thus carry more expressive potential. Drawing upon corpus data, this paper addresses the goal-over-source asymmetry in Korean and Thai from pragmatic and grammaticalization perspectives.